(A study on microencapsulation of pepper oleoresin by using spray drying) - Agus Sudibyo; Endah Djubaedah; Suprapto -; Nasyirudin - (Warta Industri Hasil Pertanian, 1995)
Microencapsulation of pepper oleoresin was conducted by using spray dryer in which gelatin, Tween 80, sodium alginat and dextrin were the wall material and pepper oleoresin and lecithin were the core material.The influence of solids concentration and drying condition on the product of microencapsulation and the retention of piperine and volatile oil.Drying temperature,however,may decrease the content of piperine and volatile oil in the product microencapsulated.